Rheumatic Heart Disease in Nepal: Current Scenario - KC, Man Bahadur (Nepalese Heart Journal, 2016)
Rheumatic Heart Disease, though declining in developed world, is still prevalent in Nepal in spite of increased awareness and improvement in preventive programs. This article presents the current scenario of Rheumatic Heart Disease in Nepal. Nepalese Heart Journal 2016; 13(2): 1-2